Analisis Strategi Peningkatan Penerimaan Pajak Reklame Pada Badan Pendapatan Daerah Kota Tangerang Selatan Tahun 2018-2020 - Malyda Puspita Sari; Jiwa Pribadi; Yopy Ratna Dewanti (Jurnal Ilmu Administrasi Publik, 2021)
The   research   aimed   to   discuss   the Analysis of Advertising Tax Revenue Improvement at the Regional Revenue Agency of South Tangerang City in 2018-2022. The subject of the issue in the research is determining the strategy of the Regional Revenue Agency to improve the advertising tax revenue, identify the problems,  and  the  efforts  made  to overcome those problems. The research employs a qualitative approach with a descriptive method. The researcher conducted interviews with the resources person to determine the actual conditions. Based on the research, the Regional Revenue Agency of South Tangerang City Selatan Formulated a programmatic strategy, organizational strategy resources support strategy and institutional strategy. As  a  result,  the  advertising  revenue  in 2018-2020 exceeded its target. However , the problem encountered related to the lengthy tax payment process resulted in advertising taxpayer’s compliance. The effort made by the Regional Revenue agency of South Tangerang City was developing an application and preparing new regulations that would shorten the process of advertising tax payment